Pairwise Interactions of Three Related Pseudomonas Species in Plant Roots and Inert Surfaces - Tovi, Nesli; Orevi, Tomer; Grinberg, Maor; Kashtan, Nadav; Hadar, Yitzhak; Minz, Dror (Frontiers in Microbiology, 2021)
Bacteria are social organisms that interact extensively within and between species while responding to external stimuli from their environments. Designing synthetic microbial communities can enable efficient and beneficial microbiome implementation in many areas. However, in order to design an efficient community, one must consider the interactions between their members. Using a reductionist approach, we examined pairwise interactions of three related Pseudomonas species in various micro-environments including plant roots and inert surfaces. Our results show that the step between mono and co-culture is already very complex. Monoculture root colonization patterns demonstrate that each isolate occupied a particular location on wheat roots, such as root tip, distant from the tip or scattered along the root. However, pairwise colonization outcomes on the root did not follow the bacterial behavior in monoculture, suggesting various interaction patterns. In addition, we show that inter-species interactions on a microscale on inert surface, take part in co-culture colonization, and that the interactions are affected by the presence of root extracts and depends on its source. The understanding of inter-relationships on the root may contribute to future attempts to manipulate and improve bacterial colonization and to intervene with root microbiomes to construct and design effective synthetic microbial consortia.